Kegiatan Pembuatan Komposting Padat dengan Proses Fermentasi di Desa Cianting Utara Kabupaten Purwakarta - Hakiim, Azafilmi; Latifa, Ulinnuha; Septa Hasannah, Cintiya; Agustina Sari, Dessy (Indonesian Journal for Social Responsibility, 2020)
Waste is an impurity that has no reuse value from daily human activities in both the domestic and industrial environments. One focus of the service team in this case is organic waste sourced from the domestic environment (household) by composting. The purpose of this community service activity is to create independence for the residents of Cianting Utara village in terms of organic waste management. The methodology of implementation is carried out through five stages namely identification of problems (Partner Village), compilation of organic waste management program activities, making solid composting, implementing program activities, evaluating program activities.Solid composting is done by making fermentors anaerobically, mixing composting media, and mixing household organic waste. The results of the solid composting harvest are then implemented on the tomato vegetable plant and observed. The results of the fertility level are shown based on the average length parameter 24 days maintenance 14.5 cm per plant and the number of leaves 9-15 per plant. A total of 15 respondents gave an assessment of the form distributed showing a 98% satisfaction percentage of the indicators of goal delivery, communication of material delivery, practice implementation, and question and answer knowledge. The highest indicator in the delivery of material and the implementation of questions and answers.